2019
DOI: 10.1002/imhj.21819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal reflective functioning on mothers’ and children's weight: A follow‐up study

Abstract: Based on cross-sectional research linking poor reflective functionining (RF) to eating disorders, the current follow-up study tested whether maternal RF would explain the variance of mothers' and children's weight beyond the effects of maternal emotional dysregulation. During pregnancy (Time 1 [T1]), 51 women were administered the Difficulties in Emotion Regulation Scale (DERS) and interviewed using the Adult Attachment Interview (AAI). Seven months after delivery (Time 2 [T2]), motherbaby dyads who remained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Five studies were cross-sectional and three studies were longitudinal. Across studies, the total number of participants showed great variability, with a sample size ranging from 51 [76] to 6650 participants [24]. Regarding the participating children's gender, four studies included more girls than boys, two studies included more boys, and two studies did not report on gender.…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were cross-sectional and three studies were longitudinal. Across studies, the total number of participants showed great variability, with a sample size ranging from 51 [76] to 6650 participants [24]. Regarding the participating children's gender, four studies included more girls than boys, two studies included more boys, and two studies did not report on gender.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Four studies [28,72,76,77] examined adult attachment, three studies [24,25,29] examined caregiver-child attachment and one study [78] assessed both adult attachment and caregiver-child attachment. The studies used psychometrically valid measures to assess attachment, conceptualized as either dimensional scores of attachment (n = 8), or categorical, in terms of a specific attachment style (n = 2).…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Although reflective function (RF), a highly complex mental process, is acquired after the ability to regulate emotions, these two abilities are considered to be evolutionarily interrelated [49]. Moreover, the ability to reflect on mental states enables one to communicate with their emotions in new ways [50].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to predicting the development of ED symptoms [42,51], degree of mentalization has been associated with the formation of physical complaints and somatization [48,52,53] that have been identified as potential core predictors of obesity [54][55][56]. Numerous studies have confirmed the existence of insecure attachment and impaired RF in people with EDs [50,[57][58]. The prevalence of insecure attachment among obese patients is also reported to be higher than the general population [59][60].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation